Thiamine in a wet pet food application - Molnar, Lydia (Kansas State University, 2017)
Since 2010, there have been seven recalls related to thiamine deficiency in cat food products (FDA, 2017; FSA, 2017). Cats have a high requirement of thiamine (5.6 mg/kg), and deficiencies can lead to death within a month if not treated (AAFCO, 2017). A few studies have been published regarding the impact of retort processing on thiamine loss in canned pet food but no work has been reported on heat penetration in other containers (pouches and trays). Therefore, our objectives were to determine the effect of container size and type on thiamine retention during processing of cat food. Our hypothesis was that thiamine retention would be impacted by container size and type. To address this, a 2x3 factorial arrangement of treatments in which two container sizes (small: 89-104 mL vs medium: 163-207 mL) and three container types (can, pouch, and tray) were evaluated for B-vitamin losses and thermal process lethality of a wet pet food. A model wet cat loaf type formula was produced for all six experimental treatments and each was processed in duplicate over six-days. All ingredients including the vitamin premix (10x level) were thoroughly mixed, heated to 43ºC, and containers were manually filled. The filled and sealed containers were cooked in a retort (cans: SJ Reid Retort, Bellingham, WA; trays and pouches: FMC retort, Madera, CA) with thermocouples attached to the center of representative containers (n=14) in each batch. Software (Calsoft Systems, v. 5.0.5) was used to record the internal temperatures. The retort time was targeted to meet an F₀=8 at 121ºC and 21 PSI. Treatment sample were analyzed for included pH, moisture, crude protein, crude fat, ash, and B-vitamins. Results were analyzed using the GLM procedure in SAS (v. 9.4; Cary, NC) with means and interactions separated using Fisher LSD method by significant F and an α of 5%. The proximate composition and pH were similar (P > 0.10) among treatments. There was an interaction (P < 0.05) between container size and type for time to reach the F₀=8; wherein, the medium can and tray had the longest time (45.5 and 46.3 min, respectively); the small can and tray, and medium pouch were intermediate (35.4, 36.0, and 32.0 min, respectively); and the small pouch had the shortest time (36.0 min). There was no difference for either main effect of container type or size on heating lethality values (each main effect average F₀=10.3) and total lethality ranged from 12.7-16.7 min. Thiamine retention was lowest (70%) among the B-vitamins, and there was minimal loss throughout the process. The excess heating beyond F₀=8 may account for the dramatic impact on the retention of heat labile nutrients like thiamine. This may be more difficult to control in the newer packaging systems like pouches and trays.
Keywords: thiamine; thiamine deficiency; thermocouples; retort; B-vitamins